Integrated tidal resource investigation, device, and energy tool (TRIDEnT) for multi-site, multi-device evaluation of tidal in-stream energy - Abundo, Michael Lochinvar Sim (2012)
The Tidal In-Stream Energy (TISE) is growing at a relatively fast pace. Crucial and augmentative to TISE's development is the existence of a an appropriate ecosystem of methodologies, tools, and protocols for assessment and planning of resources, technology / devices, environment, economics, installations, social impact, and policy. Current TISE evaluation rarely combine site suitability, resource assessment, and technology / device matching; and hardly can any of these tools be described as rapid, labelled as integrated nor deemed flexible. This work develops, studies, and proposes: (1) a simpler TISE metric for resource estimation, (2) a novel Tidal Resource Investigation, Device Energy Tool (TRIDenT), and (3) a method for assessing multiple sites and multiple devices using adapted power development planning criteria. Validation and benchmarking of the proposed metric and developed tool against in-situ measurement and selected methods / tools (EPRI, STEM, ESRU, GeorgiaTech) for resource assessment are done. Energy density maps are generated via TRIDEnT and are presented for four sites in the Philippines, namely: Matnog-San Bernardino Strait, Verde Island PAssage, Cebu-Santander Strait, and Davao Samal-Talicud Channel. Case studies for TRIDEnT featuring its key capabilities, such as resource analysis, device performance assessment, sire-device sustainability scoring scheme for 4 sites and 8 TISE conversion (TISEC) devices, and decision support mechanism (using depth constraints, and factoring in of power demand), are demonstrated. The TISE potential of selected sites in the Philippines is quantified for the first time. Selected TISE devices are nominated, matched, and ranked (in order of sustainability) as candidate tidal power plant installation: RTT2000, HS1000, Open-Center for Matnog San Bernardino Strait, RTT2000, Open-Center, GCK Gorlov Verde Island Passage, and RTT2000, Gen5, HS1000 for Dava Samal-Talicud Channel. Five key contributions for the field of TISE evaluation are presented in this work, namely: (1) a macro-level resource assessment using an energy potential metric based tide-height differences at the boundaries of a channel of interest; a MatlabTM-based integrated, rapid evaluation tool (2) with multiple site resource analysis (equipped with velocity histograms, frequency-intensity-direction diagrams, time-series plots, and energy density maps) capability, (4) a combined multi-site, multi-device suitability scoring scheme, and (5) a decision support system for use in pre-development / feasibility studies.